2005
DOI: 10.1111/j.1365-2249.2005.02952.x
|View full text |Cite
|
Sign up to set email alerts
|

Anisakis simplexallergy: a murine model of anaphylaxis induced by parasitic proteins displays a mixed Th1/Th2 pattern

Abstract: SummaryThe study of the singular hypersensitivity reactions to Anisakis simplex ( A.s ) proteins, may help us to undestand many of the unknown immune interactions between helmiths infections and allergy. We have developed a murine model of allergy to A. simplex , that mimics human A. simplex allergy to study the specific aspects of anaphylaxis induced by parasites. Male C3H/HeJ mice were intraperitoneally sensitized to A. simplex . Mice were then intravenous or orally challenged with A. simplex . Antigen-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 45 publications
3
39
0
Order By: Relevance
“…It was reported recently that Anisakis infections in rodents are similar to those in humans in terms of antibody and cytokine production [33,34]. As in human cases of gastroallergic anisakiasis [35], in the present study we observed that anti-t-Ani s 7 and anti-nAni s 7 IgE antibodies induced by live Anisakis larvae peaked at about day 30 p.i.…”
Section: Igg1supporting
confidence: 80%
“…It was reported recently that Anisakis infections in rodents are similar to those in humans in terms of antibody and cytokine production [33,34]. As in human cases of gastroallergic anisakiasis [35], in the present study we observed that anti-t-Ani s 7 and anti-nAni s 7 IgE antibodies induced by live Anisakis larvae peaked at about day 30 p.i.…”
Section: Igg1supporting
confidence: 80%
“…A murine model of anaphylaxis in mice sensitized by intravenous or oral challenge confirmed a mixed Th1/Th2 pattern of cytokines in both cases and anaphylaxis only in those mice intravenously challenged (31). It has been demonstrated experimentally that rats infected by a single parasite develop higher IgE levels than do rats infected with a high number.…”
Section: Innate Immune Responsesmentioning
confidence: 84%
“…Indeed, on the basis of previous reports (9,27), it could be argued that in addition to Anisakis infections, CAP FEIA detects IgE antibodies induced by free Anisakis allergens that are present in fish contaminated with this parasite and categorizes the patients as positive. However, this hypothesis appears unlikely, considering the negative results obtained in provocation test studies carried out on sensitized patients, using frozen (1,2,14), freeze-dried (32), or excretory-secretory (6) antigens, as well as in experiments conducted in a murine model of anaphylaxis (7). In consequence, it appears more likely that the large number of positive results obtained with CAP FEIA is the result of the detection of IgE antibodies induced by other allergens that share common epitopes with Anisakis allergens, as previously reported (15,18,29).…”
Section: Discussionmentioning
confidence: 99%